MIRERC018/2025: Association of eHealth Literacy with Knowledge of Social Health Authority (SHA) And Social Health Insurance Fund (SHIF) Among Undergraduate Health Students in Kenya - Kithinji, Dennis (MUST Institutional Research Ethics Review Committee (MIRERC), 2025)
The rapid expansion of digital health resources has made eHealth literacy a crucial skill for accessing and understanding health-related information. In Kenya, the Social Health Authority (SHA) and Social Health Insurance Fund (SHIF) were introduced in October 2024 to replace the National Hospital Insurance Fund (NHIF). Despite 19.3 million registrations, only 3.5 million formally employed individuals actively contribute to SHIF, suggesting hesitancy in the voluntary uptake of the program, perhaps due to knowledge inadequacies about SHA and SHIF. Yet, considering the high internet penetration in Kenya, eHealth literacy among Kenyans is presumably high. This study assesses the association between eHealth literacy and SHA/SHIF knowledge among undergraduate students in health-related courses in Kenya, who are among the Kenyans likely to have high eHealth literacy given their youthfulness and exposure to health information. An analytical cross-sectional study will be conducted with 450 students recruited via convenience sampling using an online survey. eHealth literacy will be measured using the eHealth Literacy Scale (eHEALS), while SHA/SHIF knowledge will be assessed through an adapted Kaiser Family Foundation quiz. Descriptive statistics will summarize the data on eHealth literacy levels and SHA/SHIF knowledge levels. Pearson correlation and multiple regression analysis will examine the relationship between eHealth literacy and SHA/SHIF knowledge, controlling for age, gender, year of study, and socio-economic status. Findings from this study will provide empirical insights into the role of digital literacy in health policy awareness, thus setting the ground for designing evidence-based digital literacy interventions. Furthermore, institutions of higher elearning can leverage the findings to advocacte for institutionalization of eHealth literacy to enhance SHA/SHIF public engagement strategies toward universal health coverage.